2014
DOI: 10.1186/s13099-014-0038-9
|View full text |Cite
|
Sign up to set email alerts
|

Fine tuning of virulence regulatory pathways in enteric bacteria in response to varying bile and oxygen concentrations in the gastrointestinal tract

Abstract: After entering the gastrointestinal (GI) tract on the way to their physiological site of infection, enteric bacteria encounter a remarkable diversity in environmental conditions. There are gross differences in the physico-chemical parameters in different sections of the GI tract e.g. between the stomach, small intestine and large intestine. Furthermore, even within a certain anatomical site, there are subtle differences in the microenvironment e.g. between the lumen, mucous layer and epithelial surface. Enteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…The reason for the upregulation of flrA and downregulation of tcpA could be that the flagellum increases the speed of passing through the mucus layer, while the pilus would only slow it down. When lower concentrations of bile at the epithelial surface are encountered, expression can be reversed (214).…”
Section: Choleraementioning
confidence: 99%
“…The reason for the upregulation of flrA and downregulation of tcpA could be that the flagellum increases the speed of passing through the mucus layer, while the pilus would only slow it down. When lower concentrations of bile at the epithelial surface are encountered, expression can be reversed (214).…”
Section: Choleraementioning
confidence: 99%
“…In order to counteract the detergent-like properties of bile, both commensal and pathogenic E. coli strains activate stress responses, efflux pumps, and toxin/antitoxin systems to remove bile compounds (21,30,34). Stress response genes induced by bile salts, such as sulA, are used for the cessation of cell division in order to correct damage to DNA and the membrane following oxidative stress (21,(35)(36)(37), while efflux pump mechanisms, such as AcrAB-TolC, overcome bile acid toxicity and confer resistance to bile (38). A recent study demonstrated that the MqsR/MqsA toxin/antitoxin system degrades ygiS mRNA, which encodes a periplasmic protein that promotes the uptake of the bile salt deoxycholate by the bacteria and increases stress on the bacterial membrane (34).…”
Section: Commensal E Coli and Common Bile Resistance Mechanisms Sharmentioning
confidence: 99%
“…15,16 Previously Nielsen et al 17 detected both genomospecies in patients with diarrhea, though no CONTACT Susan V. Lynch susan.lynch@ucsf.edu association between genomospecies and clinical disease severity was observed. Environmental cues in the GI tract have previously been found to trigger virulence gene expression in pathogenic bacterial species such as Vibrio cholerae, 19 and may facilitate physiological reprogramming from commensalism to pathogenic states in opportunistic microbial species. One such environmental cue is oxygen availability, which has previously been reported to influence virulence in Gram negative bacteria, 19 such as Salmonella enterica serovar Typhimurium.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental cues in the GI tract have previously been found to trigger virulence gene expression in pathogenic bacterial species such as Vibrio cholerae, 19 and may facilitate physiological reprogramming from commensalism to pathogenic states in opportunistic microbial species. One such environmental cue is oxygen availability, which has previously been reported to influence virulence in Gram negative bacteria, 19 such as Salmonella enterica serovar Typhimurium. 20 C. concisus can be cultured under microaerophilic and anaerobic conditions in laboratory settings and requires hydrogen for growth.…”
Section: Introductionmentioning
confidence: 99%